Answer:
it increase and by 16.7
Step-by-step explanation:
Step-by-step explanation:
2(2x + 1) = 3(x - 4)
4x+2=3x-12
4x-3x=--12-2
x=14
Answer:
54
Step-by-step explanation:
5-3=2
so you multiply 2 times 27.
2 times 27 is 54
Answer:
20 + 2x = 4x
Step-by-step explanation:
So you are setting the two expressions equal to each other.
buying a membership card and paying each time looks like this: 20 + 2x where x is the number of times you go to the gym. 20 dollars base then 2 each time you go.
4 each time you go is just 4x
so just set the two equal to each other.
20 + 2x = 4x
If you solve it you will get x = something, which would be the number of times to make the two equal.